2020
DOI: 10.1016/j.apgeog.2020.102280
|View full text |Cite
|
Sign up to set email alerts
|

Reducing deforestation through value chain interventions in countries emerging from conflict: The case of the Colombian cocoa sector

Abstract: Sustainability commitments by private sector actors are emerging as promising interventions to help reduce global deforestation. Much attention is placed on the forest conservation impact of these interventions in areas where commodity production constitutes a main driver of deforestation. It is however less clearly understood what role they could play in areas where the production of commodities is not evidently leading to the loss of forest, and how they could contribute to other objectives including sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Our study is not without limitations. The data we collected represents only one site per country, and did not provide enough geographical and cultivation pathways (i.e., older or newer cocoa fronts, business models across cocoa production areas, and national plans/strategies) to explain the potential role of cocoa cultivation as agent of reforestation or reforestation at country level, yet the combined methodology we described here was useful in pointing out that deforestation and cocoa cultivation cycles need to be carefully analyzed in light of the context where is grown, thus the landscape level is a key unit of analysis (Ruf, 2018;Castro-Nunez et al, 2020).…”
Section: Cocoa Expansion and Forest Replacement Pathways In Nicaragua And Perumentioning
confidence: 99%
See 1 more Smart Citation
“…Our study is not without limitations. The data we collected represents only one site per country, and did not provide enough geographical and cultivation pathways (i.e., older or newer cocoa fronts, business models across cocoa production areas, and national plans/strategies) to explain the potential role of cocoa cultivation as agent of reforestation or reforestation at country level, yet the combined methodology we described here was useful in pointing out that deforestation and cocoa cultivation cycles need to be carefully analyzed in light of the context where is grown, thus the landscape level is a key unit of analysis (Ruf, 2018;Castro-Nunez et al, 2020).…”
Section: Cocoa Expansion and Forest Replacement Pathways In Nicaragua And Perumentioning
confidence: 99%
“…Likewise, Rice and Greenberg (2000) pointed out that deforestation and cocoa cultivation cycles need to be carefully analyzed in light of the context where it is grown, for instance in alluvial soils of coastal areas of Indonesia cocoa, displaced agricultural areas, and in other cases, cocoa was planted in previously logged forested areas. More recently, a study found that cocoa farming has not been an important driver of deforestation in the main cocoa growing areas of Colombia and argued that interventions based on commodity value chain approach can support the peacebuilding process and achieve forest conservation/restoration commitments (Castro-Nunez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the tropical dry forest covers less than 1% of its original area and is considered threatened in the plains and Central Andes [78]. The rate of deforestation has increased in the last decades [79,80] due to economic activities incentivized by the national government [77,78] and illegal armed groups [59,74,75].…”
Section: Reciprocal Water Agreements (Rwa) In Central Valle Del Cauca Colombiamentioning
confidence: 99%
“…The Colombian government estimates that roughly 40% of the national territory suffers some form of degradation (United Nations Convention to Combat Desertification, 2016). Much of the degraded land represents areas affected by conflict and where the government and its development partners are promoting cacao production as an alternative to illicit coca leaf farming and, in turn, as a vehicle for reducing deforestation and building peace (Castro‐Nunez, Charry, Castro‐Llanos, Sylvester, & Bax, 2020). Research indicates that there are links between coca leaf production, deforestation and the conflict in Colombia (Castro‐Nunez, Mertz, Buritica, Sosa, & Lee, 2017).…”
Section: Year Production In Million Tons Producer Price In Usd/ionmentioning
confidence: 99%